2019
DOI: 10.2134/cftm2018.12.0101
|View full text |Cite
|
Sign up to set email alerts
|

Single Applications of Natural Postemergence Weed Control Options Do Not Provide Effective Ground Ivy Control

Abstract: More information is needed on the turf safety and efficacy of over-the-counter natural weed control products.• A single application of the tested natural weed control options will not control ground ivy.• Homeowners and turf practitioners using natural weed control options will need to differentiate between selective products safe for turf and nonselective products injuring turf before making a purchase/application. AbstractA frequent question is "What 'natural' or 'organic' herbicides (i.e., non-pesticide pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 10 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Two applications were required to control ground ivy, and other weeds like broadleaf plantain ( Plantago major ) were not effectively controlled. Patton et al (2019a) also tested an iron chelate herbicide for control of ground ivy and found that a single application only resulted in 5% control relative to the non‐treated control 32 weeks after treatment. Other biologically based selective herbicides that use plant pathogenic fungi or bacteria for turfgrass weed control do exist but are rare in the turfgrass market.…”
Section: Treatment List Active Ingredients Application Rates and Application Dates For Trial 1 Conducted From The Fall Of 2015 Through Thmentioning
confidence: 99%
“…Two applications were required to control ground ivy, and other weeds like broadleaf plantain ( Plantago major ) were not effectively controlled. Patton et al (2019a) also tested an iron chelate herbicide for control of ground ivy and found that a single application only resulted in 5% control relative to the non‐treated control 32 weeks after treatment. Other biologically based selective herbicides that use plant pathogenic fungi or bacteria for turfgrass weed control do exist but are rare in the turfgrass market.…”
Section: Treatment List Active Ingredients Application Rates and Application Dates For Trial 1 Conducted From The Fall Of 2015 Through Thmentioning
confidence: 99%
“…From this study, several non-synthetic chemical products tested could potentially provide some short-term annual bluegrass burndown. However, results were intermediate at best with little to no long-term control from most products evaluated, similar to the low weed control efficacy observed after applying non-chemical products in other turfgrass systems [8]. None of the products tested appear to provide acceptable commercial control with only a single application for this winter annual weed.…”
Section: Discussionmentioning
confidence: 65%
“…Certain products also caused short-term (1 to 2 weeks) undesirable turf phytotoxicity. Other research has found similar, non-chemical products have caused injury to desired turf as well [8,11]. Similar visual burndown is often observed after applying non-selective herbicides such as glyphosate, diquat, or glufosinate [3].…”
Section: Discussionmentioning
confidence: 71%
“…While fraise mowing is gaining some adoption, a cost analysis compared to other pest control strategies does not yet exist (Carroll et al., 2021) nor has work been done to quantify the loss of C and N from soil removed or GHG emissions. While fraise mowing is a novel cultural control tactic, other nonchemical control tactics such as solarization (Peachey et al., 2001) and flaming (Patton et al., 2019) are likewise likely to have hidden carbon costs (HCC) much greater than pesticides. As such, carefully considering the inputs and emissions of control strategies is needed before selecting the best approach.…”
Section: Management Practicesmentioning
confidence: 99%